2015
DOI: 10.1155/2015/796456
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Protein-Carbon Nanotubes on J774 Macrophages Is a Functionalization Grade-Dependent Effect

Abstract: Carbon nanotubes (CNTs) are used as carriers in medicine due to their ability to be functionalized with chemical substances. However, cytotoxicity analysis is required prior to use for in vivo models. The aim of this study was to evaluate the cytotoxic effect of CNTs functionalized with a 46 kDa surface protein from Entamoeba histolytica (P46-CNTs) on J774A macrophages. With this purpose, CNTs were synthesized by spray pyrolysis and purified (P-CNTs) using sonication for 48 h. A 46 kDa protein, with a 4.6–5.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The cytotoxic effect of CNTs functionalized with a 46-kDa surface protein was evaluated in J774A macrophages. The results showed that functionalized P46-CNTs displayed grade-dependent cytotoxicity, that is, P46-CNTs of high grade were more toxic than those of low grade [ 77 ]. Additionally, the nature of the functional protein influenced the cytotoxicity of nanoparticles.…”
Section: Main Textmentioning
confidence: 99%
“…The cytotoxic effect of CNTs functionalized with a 46-kDa surface protein was evaluated in J774A macrophages. The results showed that functionalized P46-CNTs displayed grade-dependent cytotoxicity, that is, P46-CNTs of high grade were more toxic than those of low grade [ 77 ]. Additionally, the nature of the functional protein influenced the cytotoxicity of nanoparticles.…”
Section: Main Textmentioning
confidence: 99%
“…Our results agree with this because f-CNTs did not decrease cell viability at the tested doses at 1 or 24 h of interaction in SKOV-3 or J774A.1 cell lines. These results are critical for their potential biomedical application, as the protein-CNTs bio-conjugation would decrease their cytotoxicity in in vivo models [47,48].…”
Section: Peptide Design and F-cnts Physicochemical Characterizationmentioning
confidence: 99%
“…The purification process was carried out by sonication for 48 h in a mixture of concentrated H 2 SO 4 (90%)/HNO 3 (70%), (J.T. Baker, Loughborough, Leicestershire, UK) 3:1 v/v to afford P-CNTs [17].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Our research group has demonstrated that purification processes, functionalization, and the nature of protein functionalization are important factors to consider during in vitro f-CNT cytotoxicity studies [15][16][17]. In order to be used in nanomedicine applications such as nanovaccines or drug delivery among others, in vivo studies are required to produce safer nanoparticles.…”
Section: Introductionmentioning
confidence: 99%